Random fixed point theorems on product spaces. (1993) - Beg Beg, Ismat Ismat; Shahzad Shahzad, Naseer Naseer
Abstract : The existence of random fixed point of a locally contractive random operator in first variable on product spaces is proved. The concept continuous random height-selection is discussed. Some random fixed point theorems for nonexpansive self and nonself maps are also obtained in product spaces.